2018
DOI: 10.1039/c8ra00383a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bioactivity and osteoinductivity of carboxymethyl chitosan/nanohydroxyapatite/graphene oxide nanocomposites

Abstract: The CMC/nHA/GO scaffold with the surface chemistry and roughness dual effects and the release of phosphate and calcium ions synergistically assist the mineralization and facilitate the bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 71 publications
1
32
0
Order By: Relevance
“…Table 2 shows the applications of common chitosan derivatives in bone tissue engineering. Increased pore size and mechanical properties promote osteoblast differentiation [61] Trimethyl chitosan N,N,N-trimethyl chitosan-heparin polyelectrolyte multilayer Bionic periosteum Good cell compatibility and support osteoblast differentiation [142] Hydroxypropyltrimethylammonium chloride chitosan Alginate/HACC/oyster shell powder Preparation bracket Improve mechanical properties and enhance stent surface area [143] CMCS is a commonly used in bone tissue engineering [137][138][139][140][141]. In addition to the applications shown in Table 2, CMCS can also be used to make nanofiber scaffolds [144].…”
Section: Bone Tissue Engineering Materialsmentioning
confidence: 99%
“…Table 2 shows the applications of common chitosan derivatives in bone tissue engineering. Increased pore size and mechanical properties promote osteoblast differentiation [61] Trimethyl chitosan N,N,N-trimethyl chitosan-heparin polyelectrolyte multilayer Bionic periosteum Good cell compatibility and support osteoblast differentiation [142] Hydroxypropyltrimethylammonium chloride chitosan Alginate/HACC/oyster shell powder Preparation bracket Improve mechanical properties and enhance stent surface area [143] CMCS is a commonly used in bone tissue engineering [137][138][139][140][141]. In addition to the applications shown in Table 2, CMCS can also be used to make nanofiber scaffolds [144].…”
Section: Bone Tissue Engineering Materialsmentioning
confidence: 99%
“…Stem cells from different sources could be used as progenitor cells in the process of bone formation, so their recruitment and osteogenic differentiation were key factors for effective bone regeneration. GDs were proved to have the ability of osteogenic induction, [144][145][146][147][148][149][150][151][152] as shown in Table 4. In this subsection, the signaling pathways involved in GDs-induced bone regeneration were discussed, including which signaling pathways of osteogenic differentiation of stem cells from different sources were affected by GDs and the effect of GDsrelated parameters on the signaling pathway.…”
Section: Mechanism Of Gds-induced Bone Regeneration Possible Signalinmentioning
confidence: 99%
“…In this paper, we found that the expression level of adhesive protein E‐cadherin in the annealed RGO substrate is lower than that in the unannealed substrate. Surface property can induce changes in relevant intracellular signaling pathways by modulating the expression of different adhesion proteins . Therefore, we speculate that changes in surface properties caused by different oxygen‐containing groups first changed the expression of some adhesion proteins in ESC, leading to the changes in related intracellular pathways, and ultimately, the ability of ESC to adhere, proliferate, and self‐renew.…”
Section: Discussionmentioning
confidence: 95%
“…[28][29][30]36] It has been reported that surface property may promote cell adhesion by accelerating the expression of vinculin and fibronectin. [37,38] Therefore, we speculate that changes in surface properties Adv. Surface property can induce changes in relevant intracellular signaling pathways by modulating the expression of different adhesion proteins.…”
Section: Discussionmentioning
confidence: 99%